2013
DOI: 10.1016/j.jslw.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Besides … on the other hand: Using a corpus approach to explore the influence of teaching materials on Chinese students’ use of linking adverbials

Abstract: Studies conducted on first and second language student writing in English have pointed to the latter group's high use of features such as informal language, pronouns, and linking adverbials, yet few studies have been conducted on assessed undergraduate writing produced within an English-speaking environment. This paper reports findings from a corpus study of Chinese and British students' writing in UK universities, confirming that a key area of difference is the Chinese students' higher use of particular linki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 27 publications
(36 reference statements)
6
33
0
1
Order By: Relevance
“…In Pattern 2 (N1 Be Av), the presence of an adverb made it difficult for participants to identify the pattern, although Arabic language has different types of adverbs just like in English. This finding corresponds to studies showing that EFL learners have difficulty mastering English adverbs, although they are present in their mother tongue (Leedham & Cai, 2013;Lei, 2006;Narita & Sugiura, 2006).…”
Section: Resultssupporting
confidence: 88%
“…In Pattern 2 (N1 Be Av), the presence of an adverb made it difficult for participants to identify the pattern, although Arabic language has different types of adverbs just like in English. This finding corresponds to studies showing that EFL learners have difficulty mastering English adverbs, although they are present in their mother tongue (Leedham & Cai, 2013;Lei, 2006;Narita & Sugiura, 2006).…”
Section: Resultssupporting
confidence: 88%
“…The results obtained from this current study are consistent with the previous researches that have demonstrated that the use of adverbial connectors seems to become problematic for learners because many studies reported misuse, underuse or overuse of connectors analyzing corpus and constructed examples made by native and non-native learners of English in the literature (Babanoğlu, 2014;Heino, 2010;Leedham & Cai, 2013;Milton & Tsang, 1993;Narita, Sato, & Sugiura, 2004;Yeung, 2009). One of these studies was conducted by Narita, Sato and Sugiura (2004) in order to compare logical connectors in argumentative essays.…”
Section: Discussionsupporting
confidence: 91%
“…There have been some comparative studies in terms of the use of connectors in texts of native and non-native English speakers in order to analyze them syntactically and semantically, and the patterns of use, 'misuse', 'underuse' or 'overuse' of connectors analyzing corpus and constructed examples made by native and non-native learners of English (Babanoğlu, 2014;Bell, 2010;Carrió-Pastor, 2013;Casteele & Collewaert, 2013;Leedham & Cai, 2013;Milton & Tsang, 1993;Yeung, 2009). Most of these studies demonstrated that there has been a higher frequency of overuse of the certain discourse connectors in the academic prose of non-native learners of English compared to native English speakers (Babanoğlu, 2014;Leedham & Cai, 2013;Milton & Tsang, 1993;Yeung, 2009 Nevertheless, the classifications of well-known researchers and definitions of the connective cannot explain the semantic property and syntactic positioning of the logical connector 'thus' or its register of use.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations